A room of one's own: Moments of mutual disengagement between doctor and patient in the oncology visit. Issue 5 (May 2021) - Sterponi, Laura; Zucchermaglio, Cristina; Fantasia, Valentina; Fatigante, Marilena; Alby, Francesca
Highlights: This study examines mutual disengagement in oncology visits. We employ conversation analysis to discern how mutual disengagement is achieved. Mutual disengagement is a delicate moment in the oncology visit. A successful medical encounter includes felicitous pauses in joint engagement. Abstract: Objective: This paper examines a previously neglected phenomenon in doctor-patient interaction studies, i.e. the achievement of mutual disengagement—a specific state of coordination, in which participants suspend reciprocal gaze and turn into separate axes of involvement. In the specialized setting of the oncology visit, which we consider in this study, mutual disengagement is linked to important tasks that the oncologist has to carry out, notably the scrutiny of the histological exam during the diagnostic assessment phase. Methods: Our data corpus includes 56 video-recorded oncology visits. We employ conversation analysis to discern how mutual disengagement is achieved, sustained and ended. Results: Our analysis shows that suspension of mutual engagement is a joint accomplishment that requires intersubjective cooperation. It also reveals that when talk and reciprocal engagement are suspended, intersubjective alignment is more vulnerable to breakdown. Conclusion: Our findings eschew a characterization of the oncologist as solo arbiter of the interactional exchange. An alignment with the patient is key to the felicitous accomplishment of the visit. We also suggest that a successful medical encounter is not only characterized by harmonious verbal communication, between doctor and patient, but also by felicitous pauses in their joint engagement. Practice implications: In building a room of one's own, the oncologist has the responsibility to co-construct with the patient an experience of interactional attunement and mutual understanding.